The validation of knowledge, attitude and practice questionnaire on breast cancer among women attending family medicine clinic, HUSM - Kasri, Muhd Rafiq Hj. Mohd (2010)
Introduction: Breast cancer is the leading cause of cancer deaths among Malaysian women. Breast cancer is treatable if detected early, and breast screening has proven to be the best way for early detection of breast cancer. However, poor awareness and understanding of the disease contributes to the deaths of many women in Malaysia Therefore, there is a need to develop a valid and reliable instrument to measure the knowledge, attitude and practice (KAP) on breast cancer and screening behaviours among Malaysian women. Objective: The purpose of this study was to validate the Malay language version of knowledge, attitude and practice questionnaire (KAPQ) on breast cancer among women attending Family Medicine Clinic (FMC), Hospital Universiti Sains Malaysia (HUSM). Methodology: This was a cross sectional study. The respondents were 227 women attending FMC, HUSM. They were selected using systematic random sampling. The questionnaire has been developed based on literatures and several expert opinions. The questionnaire was then self administered by the respondent. Analysis included descriptive statistics of all the study variables, determination of the construct validity using factor analysis and internal consistency reliability using Cronbach's alpha Results: All of the 227 respondents were analyzed. The mean (SD) age of the respondents was 29.6 (9.9) years. Majority of the respondents (91.6%) were Malay and nearly half of them (47.1%) were educated to upper secondary school. Factor analysis yielded five factors for knowledge domain with eigenvalue greater than one, five factors for attitude domain and only two factors for practice domain. All of the factors were loaded from 0.477 to 0.872. Meanwhile, Cronbach's alpha reliability coefficients for all domains were ranged from 0.636 to 0.818. Conclusion: The Malay language version of KAPQ on breast cancer was found to be a valid and reliable instrument to be used among Malaysian women. It can be used easily to measure the KAP on breast cancer and screening behavior, and for health promotion planning interventions. For greater applicability, it is recommended that this instrument be tested among ethnically diverse populations.